If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X(x + -2) = 3x(x + 2) Reorder the terms: X(-2 + x) = 3x(x + 2) (-2 * X + x * X) = 3x(x + 2) (-2X + xX) = 3x(x + 2) Reorder the terms: -2X + xX = 3x(2 + x) -2X + xX = (2 * 3x + x * 3x) -2X + xX = (6x + 3x2) Solving -2X + xX = 6x + 3x2 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Reorder the terms: -2X + -6x + xX + -3x2 = 6x + 3x2 + -6x + -3x2 Reorder the terms: -2X + -6x + xX + -3x2 = 6x + -6x + 3x2 + -3x2 Combine like terms: 6x + -6x = 0 -2X + -6x + xX + -3x2 = 0 + 3x2 + -3x2 -2X + -6x + xX + -3x2 = 3x2 + -3x2 Combine like terms: 3x2 + -3x2 = 0 -2X + -6x + xX + -3x2 = 0 The solution to this equation could not be determined.
| 1x+1y=114 | | xy-5=xfork | | (x+6)(4x-3)=(2x+3)(2x+3) | | 5(x-3)+7=8x-14 | | 11x-3+-2x-6=46 | | 2x^2-5x+4=3x+4 | | 2x-6x+12-16=24 | | 7.7+x=-3.6 | | 6x-3=-x-24 | | (2x)(x)=33 | | 8+7n+7=7+8n | | (2+7i)-(9-7i)= | | 2a+3a+9=44 | | 5x^2-10=4x | | x^3-7x^2-6x+30=0 | | 2x(5a+3b-8x)= | | f(x)=-8 | | 6(y-1)=36 | | 2(x+3)=3x-6 | | (2x+2)-9=0 | | (5+x)(5-x)= | | 4c=s | | (2x+2)2-9=0 | | 4x-6(-1)=18 | | f(9)=3x+7 | | sin(x-0.3226)=-0.3069 | | 3x+19=164 | | 3x+19=49 | | 9x+19=91 | | 3x+19=23 | | 8.5*4.5*3.75=143.4375 | | -8=-6-2 |